SECUENCIA CONSTRUCTIVA: QUINTA PLATAFORMA DE LA GRAN PIRÁMIDE HUACA PUCLLANA - Silvera La Torre, Hernán (2017)
The archaeological site Huaca Pucllana is located in the district of Miraflores, department of Lima, which constitutes an administrative ceremonial center, corresponding to the Lima culture. Composed of a large pyramid with 7 platforms.The fifth platform is located in the highest part of the great pyramid, these are important because they register architectural elements that are distributed and define the last 11 stages and constructive moments of the construction phase IV, located in the Late Lima period. They also show the later occupation corresponding to the Lima-Wari transition. The results provide us with information to understand the last moments of function and use of the architecture, defining architectonic elements of great complexity in the use of the space and of different constructive techniques; As well as superpositions of architectural elements, which were constantly refilled.These data demonstrate the importance of the monumental constructions Lima; The same that relate to a complex and little-known system of a political-religious organization. In the construction and the use of the space of these religious centers, they emphasize the ritual activities as a complement to the corporate work; Being the best known: rituals of breaking pots, ritual banquets, placing of human offerings, making small holes and then placing offerings. In later stages architecture undergoes changes, especially in accesses, which become much more restricted and complex; In addition the finishes of walls and floors are simple and coarse.